Analisis Perkembangan Platform E-commerce Terhadap Minat Transaksi Digital Menggunakan Metode Chi Square - Retno Palupi; Rudi Sanjaya (Infact: International Journal of Computers, 2023)
Online-based business and market behavior has become a trend due to the Covid-19 pandemic where some people, especially among students, use e-commerce to meet their needs and lifestyle. The development of science and technology is the main thing in supporting the convenience of the community to carry out online activities. People use smartphones to get the products they need, make transactions and pay online. This study analyzes the relationship between the development of various e-commerce platforms and interest in digital transactions in society, especially among students. The results of data analysis from this study become a reference for e-commerce platforms in developing their services according to market tastes. The research method used for sampling was purposive sampling methods, for data analysis using the Chi Square method from the Statistical Product and Service Solution software (SPSS version 25). From the results of the analysis of the research data, it concludes that there is a significant relationship between the development of e-commerce platforms and people's interest in conducting digital transactions.